KEMAMPUAN HOTS SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA PADA SOAL GEOMETRI - Elix Budiyanta; Aan Hendroanto; Harina Fitriyani (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2020)
Higher-order thinking (HOTS) is a high-level thinking ability in the cognitive processes that a person has in solving problems, having critical, creative, argumentative and ability skills make decisions. HOTS is one of the important competencies students have. But, in fact the results of the PISA 2018 survey show that students' scientific, literacy, and mathematical abilities in Indonesia are still weak. Therefore, this study aims to identify the extent of the ability of HOTS possessed by junior high school students in solving mathematical problems in geometry at the Literacy Contest Competition held by the Ahmad Dahlan University Mathematics Education Study Program in 2018. This study uses a qualitative descriptive study. The subject of this research was the contestants for the semi-final round of the Mathematics Literacy Contest competition which consisted of 7 teams with 3 students each. The object of this research is HOTS ability. Data analysis used qualitative descriptive analysis. The results showed that the HOTS abilities possessed by junior high school students in solving geometry problems in the Mathematics Literacy Contest race were on average less in the stages of evaluating and creating stages. Keywords : Higher Order Thinking Skill, Junior High School, Geometry. Abstrak Higher Order Thinking Skill (HOTS) merupakan kemampuan berpikir tingkat tinggi pada proses kognitif yang dimiliki seseorang dalam memecahkan masalah, yaitu keterampilan berpikir kritis, kreatif, berargumen dan kemampuan mengambil keputusan. HOTS merupakan salah satu kompetensi penting untuk dimiliki peserta didik. Namun, Faktanya hasil survei PISA 2018 menunjukkan bahwa kemampuan sains, literasi, dan matematika siswa di Indonesia masih lemah. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi sejauh mana kemampuan HOTS yang dimiliki oleh siswa SMP dalam memecahkan masalah matematika soal geometri pada ajang Lomba Kontes Literasi yang diadakan oleh Program Studi Pendidikan Matematika Universitas Ahmad Dahlan pada tahun 2018. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Subjek penelitian ini adalah para siswa SMP/MTs kelas 8 lomba Kontes Literasi matematika yang terdiri dari 7 tim dengan jumlah masing-masing tim adalah 3 siswa. Analisis data menggunakan teknik analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa kemampuan HOTS yang dimiliki siswa SMP dalam memecahkan soal geometri pada lomba Kontes Literasi matematika rata-rata kurang dalam tahapan mengevaluasi dan tahapan mencipta. Kata kunci: Kemampuan HOTS, Siswa SMP, Geometri.